Жоғары оқу орны оқытушысы имиджін қалыптастырудың өзектілігі - Хамзина, К.Б. (My University, 2016)
Under competitiveness conditions of the labour-market it is insufficient to be an expert of higher qualification, it is necessary to form a pedagogical image of a teacher. Low level of professional competence, failures in the relations in a pedagogical environment and others determine the need in the formation of a teacher image in a higher educational institution.
Keywords: image; teacher; expert; higher school